ANALISIS KUANTITATIF KELENGKAPAN DOKUMEN REKAM MEDIS PASIEN RAWAT JALAN DI PUSKESMAS CAKRANEGARA TAHUN 2021 - Januari Lesmana; Dewi Suciana (Nusadaya Journal of Multidiciplinary Studies, 2022)
Cakranegara Health Center is one of the health centers in Mataram city. This health center serves both outpatients and inpatients. Every health care institution must have a medical record document. Medical record is a file that contains records and documents about patient identity, examination, treatment, actions and other services. There is a need for quantitative analysis to see the completeness of filling out medical record documents. The purpose of this study was to determine the completeness of filling out outpatient medical record documents. This study uses a descriptive quantitative research method with a population of outpatient medical record documents and a sample of 97 medical record files with saturated sampling data collection techniques by means of checklist observations. The results of the quantitative analysis research at the Cakranegara Public Health Center were found to be incomplete in filling outpatient medical record documents. The highest incompleteness in the items of professional degrees of nurses, doctors and illegible writing is 78 medical record documents (78%), and the lowest incompleteness in name and medical record number items is 97 complete medical record documents (100%). Based on the results of this study, it is recommended for further researchers to research specifically for medical record documents in general polyclinics or specifically for one disease.